2003
DOI: 10.1051/rnd:2003008
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative status and semen characteristics of rabbit buck as affected by dietary

Abstract: International audienceThe aim of this study was to investigate the effect of dietary supplementation of long chain fatty acids (C $\geq$ 20 LCP) of the n-3 series, vitamin E and vitamin C on the antioxidant capacity of rabbit buck and on semen characteristics. Fifty male rabbits at 30 days were randomly assigned to five different diets: Control (50 mg$\cdot$kg$^{-1}$ diet $\alpha$-tocopheryl acetate), Vitamin E (200 mg$\cdot$kg$^{-1}$ diet $\alpha$-tocopheryl acetate), n-3 (2% ROPUFA oil + 50 mg$\cdot$kg$^{-1}… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
46
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 37 publications
10
46
1
Order By: Relevance
“…After storage, a general decrease in the quality of semen, regardless of the experimental treatment, was observed. Similar results have been reported previously in rabbit (Castellini et al, 2003) and fowl (Mangiagalli et al, 2007) semen after liquid storage.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…After storage, a general decrease in the quality of semen, regardless of the experimental treatment, was observed. Similar results have been reported previously in rabbit (Castellini et al, 2003) and fowl (Mangiagalli et al, 2007) semen after liquid storage.…”
Section: Resultssupporting
confidence: 92%
“…In male rabbits given drinking water supplemented with vitamin E, Yousef et al (2003) found a significant improvement in sperm volume and concentration. In contrast, Castellini et al (2001Castellini et al ( , 2003 found no positive effect on the same sperm parameters in rabbits fed a diet supplemented with vitamin E and C.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Umar et al (2010) also reported similar results when Vit C or Vit E was supplemented to rabbits. In addition, Castellini et al (2003) and Yasmina and Abdennour (2008) concluded that Vit C protected testicular tissues and sperms from mercury intoxication and inhibited the oxidative stress increased glutathione concentration and improved quality of fresh and stored rabbits' semen. In addition to the improvements in blood plasma biochemical indices, Vit C or Vit E with Se or probiotic supplementation also overcame the negative effect of 700 ppm of nitrate on seminal plasma total protein, albumin, urea, creatinine, testosterone, AST and ALT activity.…”
Section: Discussionmentioning
confidence: 99%
“…Such properties may affect the ability of the plasma membrane to accommodate the characteristic flagella motion of the sperm (Castellini et al, 2003). The function of PUFAs, particularly DHA in the testis, has been also related to their possible effects on the packing of membrane-bound receptors and activity of membrane-bounding enzymes as enzymes associated in spermatozoon-oocyte cross-talk, secondary messenger systems and membrane resistance in physical and chemical stress (Lenzi et al, 1996).…”
Section: Discussionmentioning
confidence: 99%